Inflation in Brusov–Filatova–Orekhova Theory and in its Perpetuity Limit – Modigliani – Miller Theory - Brusov, Peter N.; Filatova, Tatiana; Orehova, Natali (Journal of Reviews on Global Economics, 2014)
In this paper the influence of inflation on capital cost and capitalization of the company within modern theory of capital cost and capital structure – Brusov–Filatova–Orekhova theory (BFO theory) (Brusov et al. 2011, 2013; Filatova et al., 2008) and within its perpetuity limit – Modigliani – Miller theory is investigated. By direct incorporation of inflation into both theories, it is shown for the first time that inflation not only increases the equity cost and the weighted average cost of capital, but as well it changes their dependence on leverage. In particular, it increases growing rate of equity cost with leverage. Capitalization of the company is decreased under accounting of inflation.